Editorial - Soares, Adriana Benevides; Feijoo, Ana Maria Lopes Calvo de; Ewald, Ariane Patrícia; Mancebo, Deise; Prestrelo, Eleonôra Torres; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2010)
Adriana Benevides Soares, Ana Maria Lopes Calvo de Feijoo, Ariane Patrícia Ewald, Deise Mancebo, Eleonôra Torres Prestrelo, Rita Maria Manso de Barros